Healthcare Workers’ Knowledge and Attitude towards a Potential Monkeypox Outbreak in Pakistan: Evidence from an Analytical Survey - Ale Zehra; Sadia Shakeel; Najia Rahim; Uroosa Kawnal; Syed Shaukat Ali Muttaki Shah; Aniqa Batool; Muhammad Ali Syed (ANNALS OF ABBASI SHAHEED HOSPITAL AND KARACHI MEDICAL & DENTAL COLLEGE, 2026)
Objective: To determine the knowledge and attitude of healthcare workers (HCWs) regarding monkeypox (MPOX) and assess the association between knowledge and attitude among HCWs in Karachi.Methods: The study was conducted as an analytical survey surveying the HCWs of Karachi from 1st December 2024 to 28th February 2025 to determine knowledge and attitude of HCWs regarding MPOX.Results: A total of 380 responses were analyzed (response rate=77.3%; mean age=39.6 ± 9.5 years). The median knowledge score was 14.5 (IQR: 12.7-16.2), with higher awareness of the zoonotic origin of MPOX (87.6%), use of antivirals (>70%), and lower awareness regarding the spread from infected animals to humans (62%). There were significant knowledge-attitude correlations, and the willingness to learn about MPOX transmission (r=0.602).Conclusion: The current study provides new evidence on MPOX awareness and identifies knowledge gaps among HCWs from a metropolitan city of Pakistan (Karachi). The findings demonstrated an average knowledge score about MPOX, indicating existing awareness alongside important knowledge gaps, emphasizing the necessity of enhanced education and preparedness initiatives